The Texture Behavior of Al-Mg-Sc Alloys - Kaiser, MS (Journal of Mechanical Engineering, 2008)
Three alloys of Al-Mg with and without scandium are cold worked at different percentage and then annealed. The texture behavior of the alloys is studied by X-ray diffraction technique. The X-ray diffraction analysis is done using a PHILIPS PW1830 diffractometer with Cu-KÎ± radiation. It is found that the addition of scandium in Al-6Mg alloy influences the development of texture. The cube texture (100)[001] is preferred in the alloy in the initial stages of deformation, whereas beyond 50% deformation, the maximization of (220) intensity indicates that a mixed texture is developed on increasing the percent reduction. Keywords: Al-Mg alloys, Cold working, Annealing, Texture, X-ray diffraction. doi:10.3329/jme.v37i0.814 Journal of Mechanical Engineering Vol.37 June 2007, pp.10-17